Transition to farming - transition to milk culture - Budja, Mihael (Documenta Praehistorica, 2013)
In this paper, we discuss the transition to milk culture. While archaeological and biochemical data suggest that dairying was adopted in the Neolithic in Europe, archaeogenetic data show the absence of the allelic variant 13 910*T and very low lactase persistence in Neolithic populations in Europe. The Mala Triglavca case study shows that the Early Neolithic economy in the Caput Adriae region was mixed. It consisted of milk and processed milk, meat animal products, freshwater fish and various plants. The Vlaška group herders managed a broader spectrum of resources than exclusively ovicaprids, and were able to produce a wide range of low-lactose, storable products by fermenting milk.
Keywords: animal husbandry; arheološke najdbe; ceramic; Europe; Evropa; food; keramika; laktoza; mleko; neolitik; prehrana; živinoreja